Plant Cell Culture Protocols - Loyola-Vargas, Víctor M.; Ochoa-Alejo, Neftalí; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2012)
Cell culture methodologies have become standard procedures in most plant laboratories. Currently,  facilities for in vitro cell cultures are found in practically every plant biology laboratory, serving different purposes since tissue culture has turned into a basic asset for modern biotechnology, from the fundamental biochemical aspects to the massive propagation of selected individuals. “Plant Cell Culture Protocols, Third Edition is divided into five convenient sections that cover topics from general methodologies, such as culture induction, growth and viability evaluation, statistical analysis and contamination control, to highly specialized techniques, such as clonal propagation, haploid production, somatic embryogenesis, organelle transformation. The volume concludes with a section on the laborious process of measuring the epigenetics changes in tissue cultures.”Written in the successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, Plant Cell Culture Protocols, Third Edition seeks to serve both professionals and novices with its guide to the most common and applicable techniques and methods for plant tissue and cell culture.
An Introduction to Plant Cell Culture -- History of Plant Tissue Culture -- Callus, Suspension Culture and Hairy Roots. Induction, Maintenance, and Characterization -- Growth Measurements. Estimation of Cell Division and Cell Expansion -- Measurement of Cell Viability -- Pathogen and Biological Contamination Management in Plant Tissue Culture: Phyto-Pathogens, Vitro-Pathogens, and Vitro-Pests -- Cryopreservation of Embryogenic Cell Suspensions by Encapsulation-Vitrification and Encapsulation-Dehydration -- The Study of in vitro Development in Plants: General Approaches and Photography -- Use of Statistics in Plant Biotechnology -- Tissue Culture Methods for the Clonal Propagation and Genetic Improvement of Spanish Red Cedar (Cedrela Odorata) -- Micropropagation of Banana -- Liquid in vitro Culture for the Propagation of Arundo donax -- Production of Haploids and Doubled Haploids in Maize -- Maize Somatic Embryogenesis: Recent Features to Improve Plant Regeneration -- Improved Shoot Regeneration from Root Explants Using an Abscisic Acid Containing Medium -- Cryopreservation of Shoot Tips and Meristems: An Overview of Contemporary Methodologies -- Anther Culture of Chili Pepper (Capsicum spp.) -- Production of Inter-Specific Hybrids in Ornamental Plants -- Plant Tissue Culture of Fast-Growing Trees for Phytoremediation Research -- Removing Heavy Metals by in vitro Cultures -- Establishment of a Sanguinarine Producing Cell Suspension Culture of Argemone Mexicana  L. (Papaveraceae). Induction of  Alkaloid Accumulation -- Epigenetics, the Role of DNA Methylation on Tree Development -- The Potential Roles of microRNAs in Molecular Breeding -- Determination of Histone Methylation in Mono- and Dicotyledons Plants -- Basic Procedures for Epigenetic Analysis in Plant Cell and Tissue Culture -- Plant Tissue Culture and Molecular Markers -- Biolistic- and Agrobacterium-Mediated Transformation Protocols for Wheat -- Improved Genetic Transformation of Cork Oak (Quercus suber L.) -- Organelle Transformation -- Appendix A - The Components of the Culture Media -- Appendix B - Plant Biotechnology and Tissue Culture Resources in the Internet.
Keywords: Plant science; Botany; Cell culture; Plant Sciences; Cell Culture